Analisis Kinerja Keuangan UMKM Family Camp Outdoor dengan Menggunakan Metode Ratio Analysis (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
Financial performance analysis using the ratio analysis method is very effective for knowing the finances of a company or business, which includes both internal and external aspects. In addition, financial performance analysis functions to evaluate the financial condition of the company, which aims to make a decision on a financial problem that occurs. So that there will be improvements in financial performance in the future period. This study uses a quantitative method, focusing on the company's financial performance. The types and sources of data used are secondary data in the form of balance sheets, profit and loss statements, and data needed from 2022-2024, the data is taken from UMKM or Family Camp Outdoor businesses. UMKM located in the West Bandung Regency area is engaged in the field of outdoor equipment rental services for those who have a hobby of being active or adventuring in nature. Researchers will analyze the financial performance of this business using the ratio analysis method. The analysis used is a quantitative analysis consisting of liquidity ratios, solvency ratios, and profitability ratios. Based on the research, the research results obtained from UMKM or Family Camp Outdoor businesses have good performance. This is proven quite well using the liquidity ratio, solvency ratio and profitability ratio which results in increasing financial performance every year. The financial performance results of the Family Camp Outdoor UMKM can be said to be very good.